An overview of the recent advances in inorganic nanotubes. Issue 17 (17th April 2019) - Serra, Marco; Arenal, Raul; Tenne, Reshef
Abstract : Advanced nanomaterials and in particular nanotubes play a prominent role in nanoscience and nanotechnology developments, opening new frontiers in these areas. Abstract : Advanced nanomaterials play a prominent role in nanoscience and nanotechnology developments, opening new frontiers in these areas. Among these nanomaterials, due to their unique characteristics and enhanced chemical and physical properties, inorganic nanotubes have been considered one of the most interesting nanostructures. In recent years, important progress has been achieved in the production and study of these nanomaterials, including boron nitride, transition metal dichalcogenide nanotubular structures, misfit-based nanotubes and other hybrid/doped nanotubular objects. This review is devoted to the in-depth analysis of recent studies on the synthesis, atomic structures, properties and applications of inorganic nanotubes and related nanostructures. Particular attention is paid to the growth mechanism of these nanomaterials. This is a crucial point for the challenges ahead related to the mass production of high-quality defect-free nanotubes for a variety of applications.